Implementasi Lingkungan Sekolah yang Kondusif dalam Mendukung Pembentukan Karakter Siswa di SDN 001 Petai (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to examine the implementation of a conducive school environment in supporting students’ character development at SDN 001 Petai. Elementary schools play a strategic role not only in knowledge transmission but also in shaping students’ character through daily school practices. This research employed a qualitative descriptive approach, with data collected through in-depth interviews with the principal and classroom teachers, supported by observations of learning activities and school programs. The findings indicate that SDN 001 Petai has successfully created a conducive school environment characterized by a clean and well- organized physical setting, a positive and inclusive social climate, and active learning processes. Character development is reinforced through the consistent application of democratic values, discipline, and tolerance, as well as through the implementation of the Pancasila Student Profile Strengthening Project (P5). Teachers and the principal play a key role as role models in internalizing character values through everyday interactions and school activities. The conducive environment enables students to practice Pancasila values such as cooperation, responsibility, independence, and respect in real contexts. Overall, the results confirm that a well-managed school environment, supported by exemplary leadership and integrated character education programs, contributes significantly to students’ character formation. These findings highlight the importance of holistic school management in strengthening character education at the elementary school level.